2011
DOI: 10.1155/2011/459315
|View full text |Cite
|
Sign up to set email alerts
|

Diel Behavioral Activity Patterns in Adult Solitarious Desert Locust,Schistocerca gregaria(Forskål)

Abstract: The responses of adult solitarious desert locust to odors from a host plant were evaluated in a two-choice wind tunnel. Solitarious desert locusts collected from the field (Red Sea Coast) were more attracted to volatiles from pottedHeliotropium ovalifoliumin scotophase than in photophase. The attraction towards the host plant odors rather than to clean air, in both photophase and scotophase, concurs with previous observations on oviposition preferences near these plants. Diel behavioral activity patterns of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Solitarious and gregarious locusts express different diel patterns of activity in both the field and the laboratory (Roffey and Popov 1968; Uvarov, 1977; Michel, 1980; Steedman, 1990; Ely et al, 2011). Gregarious locusts are generally day-active, whereas activity of solitarious locusts peaks 1-2 h after dusk (Steedman, 1990; Ely et al, 2011). Evening and night activity of solitarious locusts might reduce their exposure to diurnally active avian predators (Steedman, 1990).…”
mentioning
confidence: 99%
“…Solitarious and gregarious locusts express different diel patterns of activity in both the field and the laboratory (Roffey and Popov 1968; Uvarov, 1977; Michel, 1980; Steedman, 1990; Ely et al, 2011). Gregarious locusts are generally day-active, whereas activity of solitarious locusts peaks 1-2 h after dusk (Steedman, 1990; Ely et al, 2011). Evening and night activity of solitarious locusts might reduce their exposure to diurnally active avian predators (Steedman, 1990).…”
mentioning
confidence: 99%
“…However, the daily thermocycle is determined by and synchronized with the daily photocycle. In addition, as shown by numerous authors (Ould Ely, Njagi, Bashir, El-amin, & Hassanali, 2011;Uvarov, 1977), photoperiod also directly influences TA B L E 2 Three-way analysis of variance for total distance moved (cm) and number of all jumps during 10 s, and mean distance covered during one jump (cm) for desert locust adults in the morning (07:30-09:00 hr) (ambient temperature range, 15-25°C) in winter (1966) showed that locomotor activity in S. gregaria was directly and rapidly initiated or inhibited by light vs. dark. Photoperiod also strongly influences the circadian activities of predators which presumably influence microhabitat choice and antipredator defences of locusts (see below).…”
Section: Discussionmentioning
confidence: 72%
“…However, the daily thermocycle is determined by and synchronized with the daily photocycle. In addition, as shown by numerous authors (Ould Ely, Njagi, Bashir, El‐amin, & Hassanali, ; Uvarov, ), photoperiod also directly influences grasshopper daily rhythms. For example, as early as 1966, Odhiambo () showed that locomotor activity in S. gregaria was directly and rapidly initiated or inhibited by light vs. dark.…”
Section: Discussionmentioning
confidence: 79%
“…Another important point is that gregarious phase S. gregaria behaves quite differently from solitarious phase S. gregaria (Simpson and Sword 2009 ; Ould Ely et al 2011 ). Gregarious nymphs often occupy the ground for long periods, forming large and dense aggregations that move in mass (Ellis and Ashall 1957 ; Culmsee 2002 ; Maeno et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Daily microhabitat shifting in S. gregaria probably functions in anti-predator defence, thermal regulation and feeding. Grasshoppers, including S. gregaria are attacked by diverse predators, including insects, spiders, reptiles, birds and mammals (Greathead 1963 ; Joern and Gaines 1990 ; Whitman and Vincent 2008 ; Ould Ely et al 2011 ). Predator type (e.g., mammals vs. birds; invertebrate vs. vertebrate predator) and predator-specific mortality changes throughout the 24-h period (e.g., nocturnal vs. diurnal predators), among different microhabitats (ground vs. grasses vs. trees), and as the grasshoppers grow (nymphs are often eaten by invertebrates, and adults by vertebrate predators) (Greathead 1963 ; Uvarov 1977 ; Whitman 1988 ; Whitman and Vincent 2008 ).…”
Section: Discussionmentioning
confidence: 99%